2012
DOI: 10.1021/jm300106z
|View full text |Cite
|
Sign up to set email alerts
|

Tacrine–Ferulic Acid–Nitric Oxide (NO) Donor Trihybrids as Potent, Multifunctional Acetyl- and Butyrylcholinesterase Inhibitors

Abstract: In search of multifunctional cholinesterase inhibitors as potential anti-Alzheimer drug candidates, tacrine-ferulic acid-NO donor trihybrids were synthesized and tested for their cholinesterase inhibitory activities, release of nitric oxide, vasodilator properties, cognition improving potency, and hepatotoxicity. All of the novel target compounds show higher in vitro cholinesterase inhibitory activity than tacrine. Three selected compounds (3a, 3f, and 3k) produce moderate vasorelaxation in vitro, which correl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
81
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 127 publications
(86 citation statements)
references
References 45 publications
3
81
0
Order By: Relevance
“…Based on the results of ChEs and MAOs inhibitory activity, compounds w10, 11,14,15,18,21,22 showed good inhibition. However, their ChE inhibitory activity was initially tested on enzymes of animal origin due to the lower cost.…”
Section: Inhibitory Activity Against Hachementioning
confidence: 99%
See 1 more Smart Citation
“…Based on the results of ChEs and MAOs inhibitory activity, compounds w10, 11,14,15,18,21,22 showed good inhibition. However, their ChE inhibitory activity was initially tested on enzymes of animal origin due to the lower cost.…”
Section: Inhibitory Activity Against Hachementioning
confidence: 99%
“…At present, there are three FDA-approved drugs for AD treatment, these anti-AChE agents include galanthamine, donepezil, and rivastigmine, which can only provide a temporary symptom alleviation instead of preventing or slowing the progressive neurodegeneration [21][22][23] . However, the multiple etiologies of AD make single-target strategy difficult to shed good therapeutic effect.…”
Section: Introductionmentioning
confidence: 99%
“…[18][19][20] Based on the MTDL approach, recent reports have described tacrine hybrids prepared by connecting tacrine or its derivatives to other pharmacologically relevant scaffolds with the aim of overcoming tacrine's hepatotoxicity. [21] Among these are the tacrine hybrids, such as the antioxidant tacrine-ferulic acid nitric oxide (NO) donor (hybrid 3, Figure 1), [22] or tacrine-caffeic acid (hybrid 4, Figure 1). [23] Decker and co-workers showed that tacrine-ferulic acid hybrid (TFAH) 5 a ( Figure 2) is a moderate antioxidant and a potent reversible noncompetitive AChEI.…”
Section: Introductionmentioning
confidence: 99%
“…Anthranilic acid 1 was condensed with cyclohexanone 2 to yield chloro acridine 3 38,39 . Treatment of 3 with different diamine led to 4-8, which were condensed with cinnamic acid to result in the target compounds 9-13.…”
Section: Compound Design and Chemistrymentioning
confidence: 99%
“…Compared to 12, the activities of the three compounds on AChE were remarkably reduced, while the BuChE activities were maintained. In addition, we synthesised three derivatives with 3-OMe-4-OBn substitution (36)(37)(38) on the cinnamic acid moiety, they also exhibited much reduced activities against ChEs. As the binding site of BuChE was larger than AChE, we inferred that the large benzyloxy group can be tolerated by BuChE, while it was repelled by AChE.…”
Section: Ches Inhibitory Activity and Sar Analysismentioning
confidence: 99%